Bruceshield: Internet of things integrated biometric and food detection system to eradicate brucellosis milk contamination - Tirtono, Jasa Dwi; Prashanti, Lupita; Saputra, Raphael Abel; Suputra, I Gede Wahyudi; Permatasari, Dian Ayu (Social Agriculture, Food System, and Environmental Sustainability, 2025)
Background: Brucellosis is a zoonotic infectious disease caused by the bacteria of the genus Brucella spp. that causes abortion and chronic disease in animals and humans, resulting in economic losses worldwide. Brucellosis remains endemic in ruminant livestock in Indonesia, with a prevalence rate of 40% in ruminants and the highest incidence of cases is in Java Island. Vaccination, livestock movement monitoring, and diagnostic methods such as PCR can prevent this disease, but those methods are challenged by cost and a lack of trained personnel. Methods: The methodology used in this article is a literature review. Design ideas were identified from various international and national journal literature with the main focus on test methods consisting of Multiple Cross Displacement Amplification - Lateral Flow Biosensor (MCDA-LFB) test, Retinal Biometric system, Static QR-Code system, and Internet of Things (IoT). Findings: Bruceshield is a complete entity combining animal retinal biometrics, food detection using MCDA-LFB technology, and IoT for accurate identification, rapid detection, and effective data collection of IoT-ready devices. Some of these methods include MCDA-LFB for DNA analysis, retinal biometric systems for animal identification, and static QR codes that report parasite detection and enable traceability to the consumer in dairy products. Conclusion: Bruceshield presents an innovative solution to support the vision of 'Brucellosis Free Indonesia 2025' by integrating advanced diagnostic and monitoring systems, contributing to Sustainable Development Goal (SDG) number 3 and the One Health paradigm. This system holds the potential to enhance disease prevention, improve livestock traceability, and promote transparency and safety within the dairy and livestock industry. Novelty/Originality of this article: This study introduces Bruceshield, an integrated system combining retinal biometrics, MCDA-LFB technology, and IoT for accurate livestock identification, rapid disease detection, and effective data collection.